Intracervical and intrauterine sperm penetration in the functional cervical factor infertility - Kesseru Koos, Esteban (2015)
In 14 women with cervical factor infertility functional postcoital tests preovulatory 30 days, with accurate counts of spermatozoa in mucus cervicaI and intrauterine contents were made. The values are compared with the breasts of 19 women, multiparous. A normal patient and two infertile were followed with serial through a full cycle. Exact quantification of mucus crystallization, made by a new method, proved to be a good criterion for evaluating the cervical penetrability. A intracervical level infertile group results were not significantly different from controls; a slight decrease of mobile sperm directional no practical value. By contrast, intrauterine level in infertile sperm group were detected in only 7 of the 30 cases with very low concentrations; in the control group were 18 of 19 cases. It emphasizes the value of intrauterine sperm count, much higher than intracervical tests. The technique allows more accurate than those reported in the literature quantitative results. Treatment consisted mainly of low dose estrogen to 8 or 14 days cycle. improving the quality of mucus in 11 patients and pregnancy in 8 (57%) it was achieved.